Bouvard et Pécuchet et le savoir médical - Norioki Sugaya (Flaubert: Revue Critique et Génétique)
This article proposes to study the medical documents gathered by Flaubert for the preparation of Chapter III of Bouvart et Pécuchet. This substantial file, which contains reading notes taken by the novelist for the writing of the medical chapter, allows us to understand to what extent the “comic of ideas”, characteristic of the encyclopedic novel, is the result of an intensive work on knowledge. Indeed, the novelistic writing of Bouvard explores the epistemological configurations of each discipline, and in particular reveals its aporia and its insufficiencies. We have chosen to focus on the medical file in order to understand the meaning of the documentary excess with respect toFlaubert’s esthetics. First we shall study the components of the file, identifying the medical works read by the author of Bouvard. Then we will examine Flaubert’s critical reflection on knowledge, in particular the way he hunts down and constructs contradictions. Finally, we will analyze an episode in the novel, that of Gouy’s typhoid fever. We shall study its genesis which will show the presence of the epistemological in the art of the novel.